Spatial heterogeneity and influence mechanisms on soil respiration in an old-growth tropical montane rainforest with complex terrain - Yang, Huai; Huang, Ting; Li, Yide; Liu, Wenjie; Fu, Jialin; Huang, Biao; Yang, Qiu (Frontiers in Ecology and Evolution, 2023)
Although numerous studies have investigated ecosystem-scale soil respiration (SR) at different ecosystem, our understanding of spatial heterogeneity of SR at plot scale is still incomplete, especially in tropical rainforests with complex topography. Further, the ecological factors that drive the variability in respiration in tropical rainforests is also poorly understood. Here, we investigated the spatial variations and control mechanisms of SR in a 60-ha plot of old-growth tropical rainforest with complex topography. Specifically, we sampled a 60-ha plot in intervals of 20 m to measure SR. The mean SR rate in this plot was 4.312 ± 0.0410 (SE) μmol m-2s-1. Geostatistical analysis indicated that the SR rate at this plot had a moderate spatial dependence, with a nugget-to-sill ratio of 68.1%. The coefficients variance of SR was 36.2% and the patch size was approximately 112 m. Stepwise linear regression analysis (involving a multiple regression tree) revealled that the independent factors regulated different types of SR’s. Liner mix-effect models showed that SR was significantly positively related to soil phosphorus and negatively to the slope in the 60-ha plot. Spatial disturbance of SR along multidimensional habitats that an increase in elevation of the multidimensional habitat, which was accompanied by enhanced SOC and soil phosphorous, also increased its SR in the 60 ha plot. This study would be helpful in designing future field experiments for a better understanding of SR at plot scale.